The original judo information site
The Judo Information Site went online in June 1995. It is one of the oldest martial arts sites online, and the first site to provide a wealth of information about any martial art. The Judo Information Site is the original, often-copied, information source. The purpose of the Judo Information Site is to promote Judo around the world by educating the general public and Judo students about the various benefits of Judo. Judo can be more than an Olympic sport or a martial art. It is a way of life for many people who practice it. This site allows the learning to continue off the mat, providing a reference tool for students and coaches to gain a more complete understanding of the richness of Judo. Contents: What is judo? Frequently asked questions Techniques of judo Articles: History, principles, research and more Competition and training Find a judo club and Links Shop: Books, uniforms, shirts, more Humor Judo forum